Risk factors for atherosclerotic cardiovascular disease (ASCVD) in healthcare professionals of Azar Cohort Study: A cross-sectional Study - Neda Roshanravan; Helda Tutunchi; Rezayat Parvizi; Sepideh Bastani; Mohammad Asghari Jafarabadi; Elnaz Faramarzi; Naimeh Mesri Alamdari; Zohreh Ghoreishy; Faezeh Tarighat; Kazem Mehravani; Milad Vahedinezhad; Nazli Namazi; et al. (Tabriz University of Medical Sciences, 2024)
Background: Atherosclerotic cardiovascular disease (ASCVD) is considered a worldwide health problem associated with high morbidity, mortality, and cost of care. In the present study, we examined risk-enhancing factors for ASCVD in healthcare workers of the AZAR cohort population. Methods: Data from a total of 500 participants were used for this cross-sectional study. Demographic characteristics, anthropometric indices, biochemical factors, and blood pressure were assessed. To evaluate the associations of ASCVD with the parameters mentioned above, univariate and multivariate logistic regression analyses were conducted. Results: The total frequency of subjects with severe (≥7.5) and low (<7.5) ASCVD was 7.6% (95% CI: 5.4-10.3), and 90.6% (95% CI: 87.7-93.0), respectively. The top strongest links were found between ASCVD and atherogenic index of plasma (AIP) (odds ratio [OR]: 12.8, 95% CI: 3.2-49.9), diabetes (OR: 7.6, 95% CI: 2.8-25), and daily smoking (OR: 7.0, 95% CI: 2.8-20). Based on a multivariate logistic regression model, low-density lipoprotein cholesterol (LDL-C)/apolipoprotein B (Apo b), diabetes, hematocrit, age, Triglycerides (TG)/high-density lipoprotein cholesterol (HDL-C), systolic blood pressure, HDL-C, apolipoprotein A-I (Apo A-I), hemoglobin, and Apo B/Apo A-I have significant associations with ASCVD severity. Conclusion: In conclusion, the present study showed significant associations between the severity of ASCVD with some parameters among healthcare workers of AZAR cohort study.